Reverse Fosbury Flop Tear of the Rotator Cuff - Jérôme Tirefort; Gregory Cunningham; Alexandre Lädermann (Case Reports in Orthopedics)
Introduction. “Fosbury flop” tear is an avulsion of the posterosuperior rotator cuff from the bone with reversal healing on its medial bursal-side. This case report describes a unique variant of Fosbury flop tear with a lesion of the musculotendinous junction that healed, for its tendon part, on the anterior humerus and coracoid process. Case Presentation. A 62-year-old man developed a posttraumatic painful shoulder with active loss of range of motion. Magnetic resonance arthrography demonstrated a lesion of the musculotendinous junction of the supraspinatus with healing of the tendon on the above-mentioned structures (reverse Fosbury flop). During arthroscopic evaluation, tendon repair was not possible and a debridement to avoid subacromial and anterior impingement associated with a tenotomy of the long head of the biceps were carried out. One year postoperatively, the patient had complete range of motion and was satisfied with the clinical results. Discussion and Conclusion. Different Fosbury flop tears exist. Radiologists and orthopedic surgeons should be aware of these tear patterns as failure to recognize them may lead to inadequate treatment.